The Effect of Corporate Intangible Assets and Audit Quality on Transfer Pricing Practices in Multinational Companies in the Consumer Non-Cyclicals Sector Listed on the Indonesia Stock Exchange (IDX) for the 2020-2024 Period - Muhammad Fakhri Imaduddin; Memed Sueb; Nanny Dewi Tanzil (Green Publisher Indonesia, 2025)
The study was conducted with the aim of determining the impact of intangible assets and audit quality on transfer pricing practices in Multinational Companies listed on the IDX for the 2020-2024 Period of the Consumer Non-Cyclicals Sector. The research method used was multiple regression analysis. The results of the study showed that there was a partial positive influence by the intangible asset variable on transfer pricing but there was no partial effect by the audit quality variable on transfer pricing. The results of the study also show that there is a simultaneous influence of the intangible asset variable and audit quality on transfer pricing.